Altitude-adaptive water use strategies of grassland are constrained by air dryness and stoichiometry in southwest of China - Bai, Jiankun; Zhai, Deping; Xu, Yang; Chen, Deyun; Wang, Wei; Xu, Ziyue; Si, Yuhui; Yang, Fujia; Sun, Mei; Zhang, Yinfeng; Chen, Zhigang; Yang, Juan; et al. (Frontiers in Plant Science, 2026)
IntroductionUnderstanding the elevational patterns of intrinsic water-use efficiency (iWUE) and their drivers is crucial for predicting plant adaptation and ecosystem responses to climate change. However, how iWUE in different photosynthetic pathways (C3 vs C4) varies with elevation, which is interactively shaped by climate and nutrient constraints remains unclear.MethodsHere, we integrated stable carbon (δ13C) and oxygen (δ18O) isotopes with plant-soil stoichiometry across a grassland elevation transect to interpret these mechanisms.ResultsOur results reveal a fundamental divergence in the response of iWUE to elevation: iWUE increased significantly in C₃ grasses but decreased slightly in C4 grasses. Using a machine learning approach, we identified vapor pressure deficit (VPD) and leaf stoichiometry (C:P and N:P ratios) as key drivers to shape the altitudinal patterns of iWUE. However, these factors exhibited opposing effects: VPD was negatively correlated with iWUE in C3 species but positively correlated in C4 species.DiscussionThese contrasting patterns reflect distinct eco-physiological strategies. C3 plants improve iWUE under the cooler, potentially nutrient-limited in high-elevation conditions through conservative resource-use traits. In contrast, the CO2-concentrating mechanism of C4 plants appears constrained at lower temperatures, limiting their iWUE. Our findings demonstrate that iWUE patterns are not simply climate-driven but emerge from pathway-specific interactions between climatic gradients and nutrient availabilities. This study provides a mechanistic framework for forecasting shifts in grassland community structure and carbon-water fluxes under future climate change.